Analisis Penerapan Prinsip Etika Bisnis Islam Dalam Pengelolaan Produksi dan Penjualan UMKM Oleh-Oleh Khas Tembilahan - Sindy Malisa Sari; Nurlia Fusfita; Ogi Saputra (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in promoting national economic growth by creating employment opportunities, increasing community income, and strengthening regional economies. However, MSMEs continue to face various challenges, including limited capital, inadequate human resources, low digital literacy, and the suboptimal implementation of Islamic business ethics. This study aims to analyze the implementation of Islamic business ethics principles in the management of production and sales within MSMEs based on the available research document. The study employs a qualitative approach with a case study design through an analysis of the concepts of Islamic business ethics, stakeholder theory, maslahah theory, and the management of production and sales as presented in the source document. The findings indicate that the principles of tawhid (unity), honesty, justice, responsibility, and maslahah serve as essential foundations for conducting business activities in accordance with Islamic law. The implementation of these principles enhances consumer trust, strengthens relationships with stakeholders, and supports business sustainability. Nevertheless, their implementation is constrained by several factors, including limited understanding of Islamic ethical principles among business actors, insufficient capital, low digital literacy, and inadequate guidance and institutional support. Therefore, stronger collaboration among MSME owners, government agencies, educational institutions, and Islamic organizations is necessary to reinforce the implementation of Islamic business ethics through training programs, business mentoring, and supportive policies. Such collaborative efforts are expected to improve the competitiveness and sustainability of MSMEs while contributing to broader social welfare in accordance with the objectives of the Islamic economic system.